2021
DOI: 10.3390/ijerph18094714
|View full text |Cite
|
Sign up to set email alerts
|

The Whitening Effect and Histological Safety of Nonthermal Atmospheric Plasma Inducing Tooth Bleaching

Abstract: Various light sources have been applied to enhance the bleaching effect. This study was to identify the histological evaluation in oral soft tissues, as well as tooth color change after tooth bleaching by nonthermal atmospheric pressure plasma (NAPP). Nine New Zealand adult female rabbits were randomly divided into three groups (n = 3): group 1 received no treatment; group 2 was treated with NAPP and 15% carbamide peroxide (CP), which contains 5.4% H2O2, and group 3 was treated with 15% CP without NAPP. Color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Tukey's post hoc test indicated a statistical substantial variation between control group and each of the other groups. Table (1) and figure (2,3). (0.202±0.011), with the least value recorded in ascorbic acid group (0.029±0.008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tukey's post hoc test indicated a statistical substantial variation between control group and each of the other groups. Table (1) and figure (2,3). (0.202±0.011), with the least value recorded in ascorbic acid group (0.029±0.008).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of tooth whitening using peroxides occurs by penetration of peroxide through the porosities of enamel prism to the dentin. Oxidation and formation of free radicals lead to lighten of colored species and achieve rapid aesthetic results (1) .…”
Section: Introductionmentioning
confidence: 99%
“…The RONS produced by LTP has been considered playing important roles in antimicrobial processes and surface modification, and also known to cause oxidative and nitrosative stress to cells and tissue. Nam et al recently conducted a histological safety study in a rabbit model using an LTP for tooth bleaching [183]. The LTP was based on a DBD configuration, powered by 15 kHz ac at 10-kV peak voltage.…”
Section: B Challenges and Proposed Solutionsmentioning
confidence: 99%
“…The working gas was Ar. The gap temperature was about 35 • C. The study concluded that the combinational treatment of plasma and 15% carbamide peroxide (CP) resulted in the most color change compared with 15% CP treatment alone, and the combination treatment did not indicate inflammatory responses nor thermal damages [183]. Nam et al also noted that the plasma did not cause histological damage in oral soft tissues during tooth bleaching [183].…”
Section: B Challenges and Proposed Solutionsmentioning
confidence: 99%
See 1 more Smart Citation